2003
DOI: 10.1159/000070271
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Prognosis of Stroke and TIA: The Need for High-Quality, Large-Scale Epidemiological Studies and Meta-Analyses

Abstract: Stroke is a considerable clinical, social and economic burden. In recent clinical trials, a number of strategies have been shown to reduce the risk of stroke and transient ischaemic attack (TIA) in both primary and secondary prevention settings. Whether these treatments are leading to a significant reduction in the incidence of first and recurrent stroke in the clinic, however, remains unclear due to a paucity of high-quality epidemiological data. A similar lack of reliable epidemiological studies has undermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 71 publications
1
25
0
1
Order By: Relevance
“…described previously, 17 and direct assessment has shown that caseascertainment is near complete. 18 All cases were reviewed by a neurologist to confirm the diagnoses, which were based on standard criteria.…”
mentioning
confidence: 51%
“…described previously, 17 and direct assessment has shown that caseascertainment is near complete. 18 All cases were reviewed by a neurologist to confirm the diagnoses, which were based on standard criteria.…”
mentioning
confidence: 51%
“…Approximately 15-20% of ischaemic strokes are preceded by a TIA 117 and the appropriate detection and urgent diagnostic work-up for patients with TIA can avoid a further disabling stroke if the correct treatment is indicated. A retrospective study of consecutive patients attending emergency departments (EDs) within 24 hours after TIA demonstrated that the stroke risk after the index event was higher than previously thought; the stroke rate was 10.5% at 90 days, with half of the events (5.3%) occurring within 2 days of symptoms onset.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such variations in results, which might be perceived as a lack of reliable evidence, might hamper the effective provision of services and treatment. 40 To ascertain the validity of costing studies of cerebrovascular diseases and to make results more comparable across studies, this review set out a number of criteria that studies should ideally fulfill.…”
Section: Luengo-fernandez Et Al Cerebrovascular Disease Costs E21mentioning
confidence: 99%